CRITICAL REVIEW OF FOREIGN RESEARCHES OF THE VALUES ROLE IN ORGANIZATIONAL CHANGES - N. Yu. Lebedeva (Publishing House of the State University of Management, 2019)
A review of the literature on change management of foreign researchers on the relationship of organizational values and the success of organizational changes has been presented. Identification instruments of organizational values have been considered. Typology of organizational culture on eight value systems in accordance with Graves’ emergent cyclical levels of existence theory and the concept of spiral dynamics by Beck and Cowan has been proposed. Characteristic of organizational culture depending on the level of value structure development has been given.